Language Teacher Proficiency Assessment: Models and Options - Briguglio, Carmela; Kirkpatrick, Thomas (Australian Federation of Modern Language Teachers Associations Inc., 1997)
In 1996, The Curtin University Centre for Literacy Culture and Language Pedagogy was commissioned by the Education Department of W A (EDWA) to undertake a project which would gather information on developments in the area of language teacher proficiency assessment in the various Australian States and Territories and provide advice to the Department in this area. The project examined issues of language teacher supply and demand at the national level and the resulting State and Territory responses. It also examined issues surrounding proficiency, including questions of measurement, assessment and implementation. This paper is based on the findings of that project.